2007
DOI: 10.1158/0008-5472.can-07-0326
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Eg5 Causes Genomic Instability and Tumor Formation in Mice

Abstract: Proper chromosome segregation in eukaryotes is driven by a complex superstructure called the mitotic spindle. Assembly, maintenance, and function of the spindle depend on centrosome migration, organization of microtubule arrays, and force generation by microtubule motors. Spindle pole migration and elongation are controlled by the unique balance of forces generated by antagonistic molecular motors that act upon microtubules of the mitotic spindle. Defects in components of this complex structure have been shown… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 53 publications
4
119
0
2
Order By: Relevance
“…It is thus possible that at least part of Nek7 À/À mitotic phenotypes are due to a disturbance in one or more of the multiple mitotic tasks performed by Eg5 (Walczak et al, 1998). Interestingly, overexpression of Eg5 in transgenic mice resulted in tetraploidization, aneuploidy and high incidence of cancers (Castillo et al, 2007). Tetraploidization has recently been suggested as a major route to aneuploidy (for review, see Storchova and Kuffer, 2008).…”
Section: Nek7 Kinase Targeting Leads To Polyploidy H Salem Et Almentioning
confidence: 99%
“…It is thus possible that at least part of Nek7 À/À mitotic phenotypes are due to a disturbance in one or more of the multiple mitotic tasks performed by Eg5 (Walczak et al, 1998). Interestingly, overexpression of Eg5 in transgenic mice resulted in tetraploidization, aneuploidy and high incidence of cancers (Castillo et al, 2007). Tetraploidization has recently been suggested as a major route to aneuploidy (for review, see Storchova and Kuffer, 2008).…”
Section: Nek7 Kinase Targeting Leads To Polyploidy H Salem Et Almentioning
confidence: 99%
“…We have to note that although transient transfections in HeLa cells were successful in the period of 36 h, we were unable to raise permanently transfected clones expressing either wild type or any of the Eg5 mutants. One possible explanation for our inability to raise stable expressing clones may come from the recent observation in the mouse model showing that overexpression of Eg5 resulted in tumorogenesis which was associated with chromosome instability due to perturbations of mitotic spindle assembly [36].…”
Section: Expression Of Eg5 Point Mutants In Cellsmentioning
confidence: 99%
“…In nonproliferating cells and tissues in adults, the expression of KSP remains undetectable, whereas its expression is prominent in proliferating cells and tissues during development. 20,55 Increased expression of Eg5 reportedly is associated with tumorigenesis. For example, Castillo et al 20 demonstrated that transgenic mice that overexpressed Eg5 were prone to the development of a variety of tumors.…”
Section: Kinesin-5 Familymentioning
confidence: 99%
“…For example, alterations of KIF3, 13 KIF1B, 14 KIF14, 15 and Kid 16 proteins were observed in breast cancer; KIF14 17 and KIF4A 18 were altered in lung cancer; and KIF1B was down-regulated in neurofibroma. 19 In addition, altered expression of EG5, 20 CENP-E, 21 KIF5B, 22 and KIF18A 23 proteins was associated with the development of different human cancers. Thus, an analysis of their expression may serve as useful tools for the early detection of tumorigenesis and for better predictions of prognosis for patients with cancer.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation